Rates and causes of rejection in blood donors from a peruvian hemotherapy center in the context of the COVID-19 pandemic - López-Pilco, Kimberly Ruth (2025)
Objetive: To determine the proportion, relationship and main causes of rejection of blood donors in the Hemotherapy Center of the Regional Teaching Hospital of Trujillo in the context of the COVID-19 pandemic 2020 to 2021. Methods: Research descriptive, retrospective, cross-sectional, in donors who attended the Hemotherapy Center of the Regional Teaching Hospital of Trujillo in the context of the COVID-19 pandemic between March 2020 and March 2021. Data collection was carried out using the care records of the blood bank service applicants. Results: A predominance of the male sex (74.4%), Rh + blood type (97.1%) and blood group “O” (79.4%) was found. Furthermore, the majority of donors had an average age of 33 years, were considered suitable to donate (69.6%), were new donors (66.1%) and replacement donors (95.0%). Likewise, the main causes of refusal to donate blood were a low hematocrit level (14.3%), risk behavior (12.1% and having some respiratory pathology (11.9%). In the same way, the multivariate analysis confirms that the hematocrit, Rh type and age are associated with the highest frequency of rejection. Conclusion: Hematocrit, Rh type and age were associated with the highest frequency of rejection in donors who attended the Hemotherapy center of the Regional Teaching Hospital of Trujillo in the context of the COVID-19 pandemic 2020 to 2021.